2001
DOI: 10.1002/dvdy.1185
|View full text |Cite
|
Sign up to set email alerts
|

Msx2 is a repressor of chondrogenic differentiation in migratory cranial neural crest cells†

Abstract: During early mouse embryogenesis, cranial neural crest cells (CNCC) emigrate from the posterior midbrain and rhombomeres 1 and 2 of the anterior hindbrain into the first branchial arch-derived maxillary and mandibular processes and there provide cell lineages for several phenotypes, including cartilage, bone, and tooth. Here, we report that Sox9 and Msx2 were coexpressed in a subpopulation of CNCC during their migration. Because Sox9 is a transactivator of chondrogenesis, and Msx genes can act as transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 56 publications
4
62
0
Order By: Relevance
“…In mammals, Bmp2, Msx2, Sox9, Col2a1, Runx2 and Col1a1 interact in the developmental pathway leading from neural crest to cartilage and bone (Healy et al, 1999;Mori-Akiyama et al, 2003;Takahashi et al, 2001). Zebrafish has duplicate copies of these six genes (Chiang et al, 2001;Ekker et al, 1997;Fisher et al, 2003;Flores et al, 2004;Martinez-Barbera et al, 1997;Postlethwait, 2004;Yan, et al, 1995;Yan et al, 2002), and we have begun to investigate their regulatory interactions to test the parallel and network models for the evolution of developmental pathways after genome duplication.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, Bmp2, Msx2, Sox9, Col2a1, Runx2 and Col1a1 interact in the developmental pathway leading from neural crest to cartilage and bone (Healy et al, 1999;Mori-Akiyama et al, 2003;Takahashi et al, 2001). Zebrafish has duplicate copies of these six genes (Chiang et al, 2001;Ekker et al, 1997;Fisher et al, 2003;Flores et al, 2004;Martinez-Barbera et al, 1997;Postlethwait, 2004;Yan, et al, 1995;Yan et al, 2002), and we have begun to investigate their regulatory interactions to test the parallel and network models for the evolution of developmental pathways after genome duplication.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic hybrid knockout studies of murine Twist-1/Msx2 heterozygotes showed that these animals displayed enhanced differentiation and proliferation of the frontal bone skeletogenic mesenchyme [53] where Msx2 is known to be highly expressed by proliferating osteogenic cells [54]. In addition, this transcription factor has been shown to be both an inhibitor and promoter of osteoblast differentiation [53,[55][56][57], and has been reported to inhibit chondrogenesis by acting as a repressor of Sox9 [58]. Collectively, these data suggest that Twist-1 and Dermo-1 may act to regulate critical transcription factors and osteo/ chongrogenic inductive factors that are important in the early events for determining cell fate decisions in human MSC populations.…”
Section: Discussionmentioning
confidence: 99%
“…In skeletogenesis, Msx2 is an inhibitor of chondrogenesis and is involved in controlling bone morphogenesis. 27 In developing long bones, Msx2 is present in the resting and proliferative chondrocytes of the growth plate and auricular cartilage, perichondria, and osteoblasts. 20 Unexpectedly, the Msx gene expression did not seem to have an eminent role in cranial base development.…”
Section: Discussionmentioning
confidence: 99%